Psychoanalysis (continued) - Delgado, Honorio F. (1919)
Our psychoanalytic experience, the staff at this reduced autognosis not authorize us to do destructive criticism of the theories of Freud. In the lines that follow, try, if you fit them into a more general scientific conception of psychodynamics: maybe this will prove a test of deductive order in favor of the established principles of psychoanalysis.